The effects of Place-Based Process Genre Module (PBPGM) on essay writing achievement among form four rural national secondary school ESL learners - Abd Halib Mohd Ali; Suyansah Swanto; Wardatul Akmam Din; Irma Wani Othman (Global Academic Excellence, 2021)
Essay writing is known to be a difficult skill among ESL learners, particularly rural students. The present study aims to measure the effects of a Place-Based Process Genre Module (PBPGM) on form four rural ESL learners’ persuasive and expository essay writing from the lens of Sociocultural Theory. A mixed-methods approach adopting a pre-test post-test control group quasi-experimental is employed to determine the significant difference and the Cohen’s d effect size. Purposive random sampling is used, and 30 students in control undergo the conventional teaching, and 30 students in the experimental group undergo a 16-hour intervention of the module. The results of the study indicate that there are significant differences and large effect sizes between the two groups. The experimental group outperforms the control group in both genres. The present study contributes to the field of teaching essay writing to rural ESL learners. The study recommends that process genre approach combined with place-based model texts be incorporated to strengthen and diversify scaffolding for teaching essay writing.